2022
DOI: 10.1177/09544089221078137
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into machinability of hardened AISI D6 steel using newly developed AlTiSiN coated carbide tools under sustainable finish dry hard turning

Abstract: In the present study, a newly developed AlTiSiN coating material deposited on carbide insert by scalable pulsed power plasma (SPPP) technique is used for machinability investigation of hardened AISI D6 die steel (65HRC) in finish dry turning. Also, the cutting tool is characterized by various diagnostic tests to evaluate the effectiveness of nanocomposite AlTISiN coating material and its cutting performance. A series of machining trials have been performed under varied cutting conditions (feed, depth of cut, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Besides the above reason, tool wear plays a significant role in chip serration. 64 From the Figure 15, it was noticed the vibration was significantly increased at the highest cutting speed. This might be the primary reason for getting more wear on the insert’s flank surface resulting prominent chip serration at higher speed range.…”
Section: Discussion Of Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides the above reason, tool wear plays a significant role in chip serration. 64 From the Figure 15, it was noticed the vibration was significantly increased at the highest cutting speed. This might be the primary reason for getting more wear on the insert’s flank surface resulting prominent chip serration at higher speed range.…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…The coating was accomplished by Oerlikon Balzers, the detailed procedure of coating deposition has been stated in the published article. 64 Cutting inserts of different nose radii having ISO specification CNMG 1204 3 3 are fastened into a tool insert holder (ISO standard: PCLNL2020K12) with tool approach angle of 95°, relief angle of 6°, tip angle of 80°, and negative rake angle of 6°. Figure 1(a) illustrates the surface morphology of coated carbide tool which revealed that AlTiSiN coating deposited by S3P method exhibited a highly dense droplet free ultra-thin film and improved surface finish of coating layer due to grain refinement of coating.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum flank wear was 60.09 µm. The presence of deep plowing grooves and edges on the flank and crater surface indicates the abrasion mode of wear of the insert [ 21 ]. Chip particles also adhered to the flank and crater surface which causes nose wear due to the welding of chips; and (ii) Figure 8 b that maximum crater wear of 44.11 µm was found by SEM.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed that: (a) 17% reduction in cutting force using the CVD tool and 13% reduction in cutting force using the PVD insert, and (b) use of MQL reduces work tool interface temperature by 5.7% by CVD tool and 6.7% by PVD respectively. While performing experimental trials of a turning operation on hardened steel, Das et al [ 20 , 21 ] concluded that the rate of feed followed by cutting speed was the influential variable for achieving the high surface finish. When the doc and cutting speed increased it resulted in higher flank wear.…”
Section: Introductionmentioning
confidence: 99%